Analysis of the Influence of Motivation and Job Satisfaction on Employee Performance in the Regional Office of the Ministry of Religious Affairs, Maluku Province - Suci Andini Slamet; Mohamad Arsad Rahawarin; Pieter Sammy Soselisa (Journal of International Multidisciplinary Research, 2025)
This study examines the influence of motivation and job satisfaction on employee performance at the Ministry of Religious Affairs in Maluku Province. Motivation and job satisfaction are critical factors that drive employee productivity and create a conducive work environment. Using quantitative methods, data were analyzed through regression tests, including T-test, F-test, and determination coefficient analysis, to explore the relationships between these variables. The results indicate that motivation has a strong and significant positive effect on employee performance, supported by a regression coefficient of 0.661 and a significance level of p < 0.001. Similarly, job satisfaction also significantly impacts performance, with a coefficient of 0.325 and p < 0.001, although its influence is comparatively lower than motivation. The simultaneous effect of motivation and job satisfaction was confirmed by an F-value of 396.748 and an R² of 0.922, indicating that 92.2% of the variation in employee performance can be explained by these two factors. The findings emphasize the importance of fostering both motivation and job satisfaction to improve employee performance effectively. Therefore, organizations should develop policies that enhance motivation through rewards and career development opportunities, as well as improve job satisfaction by ensuring supportive working conditions and recognizing employee contributions.